PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 140 PEKANBARU - Khairani Syah; Hendri Marhadi; Jesi Alexander Alim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :The purpose of this research is to improve learning outcomes IPS Elementary School fourth grade students 140 Pekanbaru with the implementation of cooperative learning model Numbered Head Together (NHT). The subjects in this study were fourth grade students of State Elementary School 140 Pekanbaru, the number of students 21 people, where men and women a total of 11 people were 10 people.The techniques of collectiont data in this study is the observation and tests. Results of research and discussion in this study shows that the learning process by implementing cooperative learning model Numbered Head Together can increase the activity of teachers and students in learning activities, where the first meeting of the first cycle of teacher activity percentage is only 65.00%. At the second meeting of the first cycle increased to 72.50%. Then in the third meeting of the second cycle increased to 90.00% and the fourth meeting of the second cycle increased be 97.50%. While the activities of students at the first meeting of the first cycle percentage is only 62.50%. At the second meeting increased be 67.50%. Then in the third meeting of the second cycle increased to 80.00% and the fourth meeting of the second cycle increased be 92.50%. The implementation of cooperative learning model Numbered Head Together can improve learning outcomes IPS Elementary School fourth grade students 140 Pekanbaru, where the base score average value of student learning outcomes is only 60.61%. Then in the second cycle increased to 66.6%7, an increase of 9.82% and in the second cycle increased to 75.24%, an increase of 23.93%. In addition, the thoroughness of student learning outcomes in classical also increased, where the base score of students who pass classically only 47.62%, on a daily tests first cycle increased to 66.67% an increase of 19.05%, and at the second cycle replicates the percentage of students in classical learning completeness increased to 80.95%, an increase of 14.28%.Keywords: NHT type cooperative learning, learning outcomes